External Indebtedness of Developing Countries - Baumgartner, Ulrich; Dillon, K.; Johnson, G.; Williams, R. (Washington, D.C. : International Monetary Fund, 1981)
The external indebtedness of non-oil developing countries has been of growing concern in recent years. Several factors have brought the debt issue to the forefront of the problems facing a number of countries, including the rapid rise in extenal debt in the recent past, changes in the composition of debt (toward a greater proportion owed to commercial banks) and the attendant deterioration in the terms of debt, and the rise in debt service resulting from these developments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet